Second Five Year Plan First Year's Achievement and Second Year's Programme Government of Kerala - Planning Commission (Planning Commission, 1957)
This book is intended to bring out in a concise form the progress in the implementation of the Second Five Year Plan of Kerala in the first year of its working and the programme approved for implementation in the second year. the issue of this publication was held up in order to see whether the Kerala Plan of which the programmes for individual years could be issued before it. It has, unfortunately not been possible so far to publish the final Kerala Plan. the reason for this is that the Kerala Plan is still under the consideration of the Planning Commission.
Government of Kerala